One new species of Marthogryllacris (Orthoptera: Ensifera: Gryllacrididae) from Yunnan, China - Chen, Xiaoqin (Zootaxa, 2024)
This paper reports one new species of Marthogryllacris from Yunnan Province, China. Marthogryllacris xiangjini sp. nov. can be distinguished by the coloration of the body and the processes of male ninth abdominal tergite.